The influence of personal resources and job stress on turnover intention among employees in the ground transportation industry - Sri Andriyani, Hernik; Chasanah, Nurul; Muhammad Alfatih, Sultan; Jannah S, Miftahul (Trigin Publisher, 2024)
This study investigates the impact of Personal Resources and Work Stress on Turnover Intention among employees in the intercity bus transportation industry, specifically drivers, assistants, and conductors. It employs a quantitative approach using Structural Equation Modeling Partial Least Squares (SEM PLS) to analyze the proposed hypotheses. The research sample comprises randomly selected employees from transportation companies in Surabaya, Madiun, Tulungagung, and Probolinggo, East Java, Indonesia.The analysis reveals significant relationships: Personal Resources significantly influence Work Stress (t=7.685, p=0.000), Personal Resources influence Turnover Intention negatively (t=-5.025, p=0.000), and Work Stress positively affects Turnover Intention (t=3.892, p=0.000). Additionally, Personal Resources indirectly influence Turnover Intention through Work Stress mediation (t=4.677, p=0.000). These findings underscore the crucial role of personal resources in managing work stress and reducing turnover intention in the intercity bus transportation sector. This research conclusion thighlights the strategic importance for companies to enhance employee personal resources to foster workforce stability and mitigate turnover intention effectively.